Identification by PCR of S‑alleles associated with gametophytic compatibility in Japanese plum - De Conti, Daniela; Ribeiro, Mirian de Farias; Raseira, Maria do Carmo Bassols; Peters, José Antônio; Bianchi, Valmor João (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to molecularly identify and characterize the S‑alleles of Japanese plum cultivars and to verify the gametophytic compatibility between them. Two pairs of specific primers were used for allele amplification by PCR in 18 cultivars: Pluma 7, Gulf Rubi, Blood Plum, Wickson, América, Santa Rosa, Rosa Mineira, Estrela Púrpura, Amarelinha, The First, Harry Pieckstone, Santa Rita, Seleção 16, Seleção A26 (Burbank), Seleção 21, Seleção 19, Methley, and Simka. PCR conditions and oligonucleotide primer combinations used allowed the identification of S‑alleles in cultivars, as well as the indication of the most compatible pollinators. América and Santa Rosa cultivars, as well as Blood Plum, Wickson, Rosa Mineira, Estrela Púrpura, and Seleção 21 show total incompatibility among each other, since they share the same alleles.
Keywords: Prunus salicina; gametophytic self‑incompatibility; S‑RNase